DINAMIKA FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PARTISIPASI ANGKATAN KERJA PEREMPUAN: PENGARUH UPAH MINIMUM, TINGKAT PENDIDIKAN DAN KEPADATAN PENDUDUK PERKOTAAN - Nabila, Vianisa; Nugraha, Handy (JURNAL ILMIAH EDUNOMIKA, 2025)
Women's participation in the labor force remains a major obstacle in the development of the labor market. In Indonesia, female labor force participation is still below male labor force participation. The purpose of this study is to investigate how the level of female labor force participation in Central Java is influenced by the regency minimum wage, women's education level, and urban population density between 2019 and 2023. The type of data in this study is secondary data from the Badan Pusat Statistik (BPS). Using panel data regression analysis with the Fixed Effects Model (FEM), this study employs a quantitative approach. The results show that female labor force participation in Central Java is positively and significantly influenced by the minimum wage, which means that if the district minimum wage increases, the participation rate of female labor in the area will also rise. However, the level of women's education and urban population density do not seem to have a significant impact on female labor force participation in Central Java. There is a need for government intervention by providing equal access to education and employment opportunities and aligning higher education levels with industry needs.